An assessment of spatial variations of land surface temperature over urban environments and anthropogenic causes: A case study of Kandy City, Sri Lanka - Sanjeewani, R.M.S.S.; Manawadu, L. (My University, 2018)
Urban sprawling pattern of most of the cities in Sri Lanka has encountered numerous socio-economic and environmental issues like increased land surface temperature over urban areas. This study identifies the spatial trends of land surface temperature (LST) over Kandy city, Sri Lanka from 1988 to 2015 and determines the anthropogenic factors contributing to increased LST variation including the impact of built-up areas, traffic count and population density. Thermal bands of Landsat TM 5, Landsat ETM+ and Landsat 8 OLI/ TRIS data are used in this study to measure land surface temperature. Accordingly higher temperature more than 300C in Kandy city is concentrated into a certain part of the Municipal Council (MC) area that is followed by the road structure of the area. Furthermore, there is a significant positive relationship between NDBI and LST in Kandy MC and the relationship is strong. Higher level of population density and traffic count have profound impact on increased LST levels.
Keywords: NDBI, Land Surface Temperature, Landsat, Population Density, Thermal Bands, Traffic Count